Relationship between Long Working Hours and Suicidal Thoughts: Nationwide Data from the 4th and 5th Korean National Health and Nutrition Examination Survey - Yoon, Jin-Ha (PLoS One, 2015)
BACKGROUND: Long working hours are a worldwide problem and may increase the risk of various health issues. However, the health effects of long working hours on suicidal thoughts have not been frequently studied. Our goal was to investigate the relationship between long working hours and suicidal thoughts in the rapidly developing country of Korea. METHODS: Data from 12,076 participants (7,164 men, 4,912 women) from the 4(th) and 5(th) Korean National Health and Nutrition Examination Surveys were used for the current analysis. Multivariate logistic regression models were used to estimate odds ratios and 95% confidence intervals for suicidal thoughts. Combined effects of long working hours and lower socioeconomic status or sleep disturbance were also estimated. RESULTS: Compared to groups who worked less than 52 hours per week, odds ratios (95% confidence intervals) for suicidal thoughts in groups who worked 60 hours or more per week were 1.36 (1.09–1.70) for males and 1.38 (1.11–1.72) for females, even after controlling for household income, marital status, history of hypertension or diabetes mellitus, health-related behaviors, and past two weeks’ experience of injury, intoxication, or acute or chronic diseases, as well as type of work. The combined effects of long working hours with lower socioeconomic status, or with sleep disturbance, were also significantly higher compared to participants who worked less than 52 hours per week with higher socioeconomic status, or with 6–8 hours of nighttime sleep. CONCLUSION: In this study, long working hours were linked to suicidal thoughts for both genders. Additionally, the odds of those suicidal thoughts were higher for lower socioeconomic groups. To prevent adverse psychological health problems such as suicidal thoughts, a strategy regarding long working hours should be investigated.